Bio-engineered microRNA-7 effectively interferes with the Akt3/p53 axis to suppress human non-small cell lung cancer - Qian Huang; Xiaohua Chu; Chaofei Yang; Ying Huai; Chenyang He; Xingcong Ma; Jiawei Pei; Junhong Gao; Zhiyong Liu; Shanfeng Jiang; Airong Qian; Ye Tian (Cancer Cell International)
Abstract Non-small cell lung cancer (NSCLC) remains the leading cause of cancer deaths worldwide. Unfortunately, effective treatment is still lacking. The p53 tumor-suppressor protein is a critical mediator of cellular growth arrest and apoptosis, and is closely related to NSCLC. Importantly, microRNAs (miRs) have been shown to influence tumor progression by targeting p53. Therefore, we screened p53-associated miRs that were differentially expressed in NSCLC and benign tissues by bioinformatic analysis. Among them miR-7 was implicated in multiple tumorigenesis related pathways. Then the novel hybrid tRNA scaffold was used to produce bio-engineered miR-7 and its inhibition to NSCLC as well as the interaction with p53 was investigated. We found that overexpression of miR-7 in NSCLC significantly inhibited the proliferation, migration, invasion, and induced apoptosis of NSCLC cells. And in vivo study exhibited dramatic inhibition of tumor growth by bio-engineered miR-7 in orthotopic NSCLC xenograft tumor mouse model. In addition, we identified Akt3 as a novel target of miR-7, the suppression of tumor growth and sensitization of chemotherapy drugs by miR-7 was related to the repression of Akt which activated MDM2-mediated ubiquitination and degradation of p53. Our results reported for the first time that miR-7 could target Akt3 and interact with genes in the p53 pathway to suppress the development of NSCLC, which also implied the therapeutic potential of bio-engineered miR-7 for NSCLC.